First record of Chrysoperla asoralis and C. argentina (Neuroptera: Chrysopidae) in horticultural fields of La Plata associated with the sweet pepper (Capsicum annuum L.) - Haramboure, Marina (2014)
Chrisopids are economically significant predators of several agricultural pests. In Argentina, the species recorded of Chrysoperla Steinmann, 1964 are C. externa (Hagen, 1861), C. asoralis (Banks, 1915), C. argentina (González Olazo & Reguilón, 2002) and C. defreitasi (Brooks, 1994). Chrysoperla asoralis and C. argentina have been associated with citric, olive, maize and cotton crops. In the present note, we record for the first time these two species in La Plata and neighboring areas within the Buenos Aires province, in association with the sweet pepper, Capsicum annuum L.